Assessment of the potential of drug-drug interactions among population-based oldest-old people in Turkiye - Özaydın,Fuat Nihat; Özaydın,Ayşe Nilüfer (PeerJ, 2025)
Background The risk of potential drug‒drug interactions is highest in oldest-old people. Thus, the aim of this study was to investigate the frequency and type of potential drug‒drug interactions in population-based oldest-old people. Methods The type of study was descriptive. Ethical permission was obtained (13.04.2022/153). All participants were informed, and their written consent was obtained. The “oldest-old” were defined as those who were ≥85 years of age during the study period and living in Turkiye. These people were reached from every region of Turkiye via the snowball method and were visited at their homes. Data were collected via face-to-face interviews. Age, sex, city of residence, and generic names of regularly used medications were recorded. The medications used were analyzed according to the Beers 2019® Criteria and UpToDate® Lexicomp® drug interaction guides. SPSS was used for statistical analysis, and p < 0.05 was considered statistically significant. Results Data were collected from the 549 oldest-old people throughout Turkiye. Among the participants, 61.2% (n = 336) were women. The median age of the women was 88.00 years (minimum = 85, maximum = 101), and the median age of the men was 88.00 years (minimum = 85, maximum = 102). The distributions of men and women in the different age groups were similar (p = 0.341). The distributions of men and women across regions were similar (p = 0.826), most of whom (n = 300, 54.6%) had ≥1 potential drug‒drug interaction, according to the UpToDate analysis. The median number of medications used continuously was 4.0 (minimum = 0, maximum = 19). The median number of potential drug‒drug interactions was 1.0 (minimum = 0, maximum = 21). As the number of medications used increased, the number of potential drug‒drug interactions also increased (r = 0.737; p = 0.001). The number of potential drug‒drug interactions decreased with increasing age (r = −0.104; p = 0.015). According to the Beers 2019® Criteria, potential drug‒drug interactions were detected in only eight patients. The concordance between the Beers 2019® Criteria and the UpToDate®Lexicomb® drug interaction data was poor compared with the number of potential drug‒drug interactions (kappa = 0.024, p < 0.001). Central nervous system medications are a common group that can cause potential drug‒drug interactions according to both guidelines. Moreover, potentially inappropriate medications defined by the Beers 2019® Criteria were the most common causes of potential drug‒drug interactions, according to UpToDate®Lexicomb® drug interactions. The frequency of potential drug‒drug interactions was found to be high in the population-based oldest-old people interviewed in Turkiye. It has been determined that the use of more than one guide in the evaluation of potential drug‒drug interactions is safer.
Keywords: Aged; 80 and over; Drug interactions; Polypharmacy; Potentially inappropriate medication list